Root architecture and carbon sequestration potential of fast-growing agroforestry tree species in semi-arid Central India - Gautam, Kamini; Kumar, Naresh; Ram, Asha; Dev, Inder; Choudhury, Burhan U.; Singh, Nongmaithem Raju; Handa, Arun Kumar; Yadav, Ashok; Anuragi, Hirdayesh; Uthappa, A. R.; Kumar, Dhiraj; Arunachalam, Ayyanadar; et al. (Frontiers in Agronomy, 2025)
Understanding the link between tree root architecture and organic carbon dynamics is critical for enhancing carbon sequestration in semi-arid regions. This study, conducted from 2017 to 2019 in central India, evaluated the root structure and carbon sequestration potential of three tree species: Neolamarckia cadamba (Kadam), Leucaena leucocephala (Subabul), and Melia dubia (Malabar neem). The species exhibited distinct root architectures: Subabul had a symmetric, sparse root system; Kadam had moderately dense roots; and Malabar neem developed a compact and massive root system. The highest root density was recorded in the 0–30 cm topsoil layer near the collar region. Primary roots initially grew vertically (0.15–0.30 m), then extended horizontally, with Malabar neem showing the widest lateral spread (up to 4.4 m). Secondary roots displayed greater angular spread than tertiary and quaternary roots. Lateral root pruning, recommended after the first two years, could enhance resource use efficiency and improve understory crop performance in agroforestry systems. Malabar neem demonstrated significantly higher carbon sequestration potential, storing 25.64 Mg C ha-¹ at three years—2.96 to 3.86 times greater than Subabul (8.62 Mg C ha-¹) and Kadam (6.62 Mg C ha-¹). Annual sequestration rates ranged from 2.20 to 2.87 Mg C ha-¹ yr-¹. Aboveground biomass contributed 80.4–84.3% of total carbon stocks, with belowground biomass contributing 15.7–19.6%. At a planting density of 500 trees ha-¹, Malabar neem achieved the highest CO2-equivalent sequestration (94.09 Mg CO2e ha-¹). These findings highlight Malabar neem-based agroforestry as a viable strategy for restoring degraded lands while improving carbon storage and climate resilience in semi-arid ecosystems.